Trends of GST Revenue and GST Registration of Business Entities and the Number of Industries as Determinants of the GST Collection in India : A Subnational Analysis - Basumatary, Joel; Hassan, Samir Ul (Arthshastra Indian Journal of Economics & Research, 2025)
Purpose : We analyzed the state-wise revenue generation from Goods and Services Tax (GST). By examining factors such as the number of industries and GST registrations, the study provided insights into the efficacy of GST in revenue mobilization of states and regional development. Methodology : A cross-sectional regression was estimated using state-wise GST revenue collection data, the number of GST registrations, and the number of industries using EViews 13 statistical software. The dependent variable is the GST revenue collection of the states, and the independent variables are the number of GST registrations and the number of industries in the respective states. To look at the year-on-year change in the revenue collection during pre-GST, the period is from 2012–2013 to 2016–2017, and the revenue generation from the GST (after the GST implementation) for the period is from 2017–2018 to 2022–2023, from the GST portal. Findings : The regression model results revealed that both the number of GST registrations and the presence of industries significantly influenced GST revenue generation across states. However, GST registrations have a more pronounced positive effect than industries. Despite excluding cesses and surcharges, GST’s share in the divisible pool steadily increased, highlighting its pivotal role in state finances. Practical Implications : State governments could take cognizance that GST registration of business entities was crucial to leverage the GST revenue collection for the states. Further, the states must have many large business entities that could enhance the GST revenue collection. Originality : This paper threw light on the GST revenue generation of the states in India. Further, it gave insights that states should focus on GST registration of the business entities, which increases the probability of increasing GST revenue collection.